Biosafety and Detection of Genetically Modified Organisms - Ferreira, Juliano Lino; Cançado, Geraldo Magela de Almeida; Borém, Aluízio; Gomes, Wellington Silva; Setotaw, Tesfahun Alemu (IntechOpen, 2012)
None